Surface hydrophobicity measurement as a tool in malting and brewing - a mini-review - Zapf, Michael W.; Vogel, Rudi F.; Ludwig Niessen, Ludwig Niessen (BrewingScience, 2006)
Foam and foam stability are indispensable signs of beer quality. Foam stability is influenced by a great number of factors. Surface hydrophobicity of proteins counts among the most crucial factors in this respect. Up to now, little use has been made of surface hydrophobicity measurements in brewing. The significance of surface hydrophobicity of proteins in food is explained, followed by a description of the principles of surface hydrophobicity and of surface hydrophobicity measurement. An overview of interrelationship of surface hydrophobicity with cosolutes, such as sugars, is given. The importance of technological and chemical influences on surface hydrophobicity and possible outcomes of surface hydrophobicity measurements in brewing science are discussed.